CONTINUAL LEARNING AS A STRATEGY FOR INCREASING REVENUE OF INDONESIAN ONLINE COMPANIES IN THE DIGITAL ERA - Ismail, Hariadi (Business Journal : Jurnal Bisnis Dan Sosial, 2024)
In the rapidly evolving digital landscape, Indonesian online companies face significant challenges in maintaining competitive advantage and maximizing revenue. This research article explores continual learning as a strategic approach to enhance revenue generation in this context. By leveraging continual learning frameworks, companies can adapt to changing market dynamics, consumer preferences, and technological advancements. The study employs a mixed-methods approach, combining quantitative data analysis with qualitative case studies of successful Indonesian online businesses that have implemented continual learning practices. Findings indicate that organizations that prioritize continual learning not only improve their operational efficiency but also foster innovation and customer engagement, leading to increased revenue streams. The implications of this research highlight the necessity for Indonesian online companies to invest in continual learning initiatives to thrive in the digital era. This article contributes to the existing literature by providing actionable insights and strategies for practitioners aiming to leverage continual learning for sustainable growth.